Computer-aided developments : electronics and communication : proceeding of the First Annual Conference on Computer-Aided Developments in Electronics and Communication (CADEC-2019), Vellore Institute of Technology, Amaravati, India, 2-3 March 2019 /: electronics and communication : proceeding of the First Annual Conference on Computer-Aided Developments in Electronics and Communication (CADEC-2019), Vellore Institute of Technology, Amaravati, India, 2-3 March 2019. (2019) - Unknown
No abstract available